UPACARA ADAT TIWAH MASYARAKAT DAYAK DI KALIMANTAN TENGAH - Bonxy, Renhat; Rochayanti, Christina; Ashriyanto, Panji Dwi (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2018)
This research is to know how the meaning of bone removal procession on Tiwah in Central Kalimantan and to know what is contained message in the procession of bone removal, this reasearch is done by doing semiotic analysis on the symbols and signs that are in procession. The type of this research is qualitative interpretative by using semiotic analysis method, semiotics is a science that examines the sign. Data collection on this reasearch using observation techniques , study of literature, interview and documentation. The technique to knowing the meaning of the bone removal process is by analyzing the signs present in the procession. Based on the results of the research we know that, the procession of bone removal on tiwah has a very deep meaning for life. This procession showing the affection and caring from dayak society to their relatives and a hope to have a better life. There is a myth like Roland Barthes says there is a myth but the truth are still unknownable the truthness. the myth of bone removal after performing ritual removal of bone is a prayer and a hope that has been presented to the Creator.